The Sedimentary Record of the Eutrophication of Lake Washington - Edmondson, W. T. (1974)
Lake Washington changed in productivity, abundance of organisms, and chemical character as a result of enrichment with sewage effluent and subsequent diversion of the effluent. A record of many of the changes is left in the sediments in the form of concentrations of specific elements or compounds and recognizable remains of organisms, especially diatoms. The vertical distribution of diatoms in dried cores of sediment can be determined with considerable precision with scanning electron microscopy. Such data provide information about the character of the lake before limnological studies were made.